1999
DOI: 10.2527/1999.773645x
|View full text |Cite
|
Sign up to set email alerts
|

Beef customer satisfaction: cooking method and degree of doneness effects on the top sirloin steak.

Abstract: The objective of this research was to evaluate the consumer-controlled factors of cooking method and degree of doneness on Top Choice, Low Choice, High Select, and Low Select top sirloin steaks. The in-home product test was conducted in Chicago, Houston, Philadelphia, and San Francisco. Consumers (n = 2,212) evaluated each top sirloin steak for overall like (OLIKE), tenderness (TEND), juiciness (JUIC), flavor desirability (DFLAV), and flavor intensity (IFLAV) using 23-point hedonic scales. Top sirloin steaks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 0 publications
1
33
0
1
Order By: Relevance
“…The majority of these studies have concluded increasing marbling level has a positive effect on beef palatability; however, the effect differs among muscles. The effect of marbling and USDA quality grade on palatability has been reported on top loin steaks (O'Quinn and others ; Emerson and others ; Corbin and others ), top sirloin steaks (Neely and others ; Savell and others ; Hunt and others ), rib steaks (Parrish and others ; Tatum and others ; Guelker and others ), top round steaks (Neely and others ; Lorenzen and others ; Behrends and others ), eye of round steaks (Smith and others ; Luchak and others ), bottom round steaks (Smith and others ), and the muscles of the chuck (Kukowski and others ; Hunt and others ). However, published reports detailing the effect of USDA quality grade on the palatability of beef tenderloin steaks are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies have concluded increasing marbling level has a positive effect on beef palatability; however, the effect differs among muscles. The effect of marbling and USDA quality grade on palatability has been reported on top loin steaks (O'Quinn and others ; Emerson and others ; Corbin and others ), top sirloin steaks (Neely and others ; Savell and others ; Hunt and others ), rib steaks (Parrish and others ; Tatum and others ; Guelker and others ), top round steaks (Neely and others ; Lorenzen and others ; Behrends and others ), eye of round steaks (Smith and others ; Luchak and others ), bottom round steaks (Smith and others ), and the muscles of the chuck (Kukowski and others ; Hunt and others ). However, published reports detailing the effect of USDA quality grade on the palatability of beef tenderloin steaks are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported as DOD increases, palatability ratings of juiciness and tenderness decrease (Cross et al, 1976;Savell et al, 1999;Lorenzen et al, 2005;Gomes et al, 2014;Lucherk et al, 2016). Juiciness ratings have been shown to have dramatic decreases (16 to 70%) when DOD was increased from lower endpoint temperatures (55 to 60°C) to higher endpoint temperatures (77 to 90°C) in multiple studies (Parrish et al, 1973;Cross et al, 1976;Lorenzen et al, 2005;Lucherk et al, 2016).…”
Section: Degree Of Donenessmentioning
confidence: 99%
“…Flores 등(1999)은 근내지방도가 다즙성과 유의적인 관련 성이 있다고 하였으며 특히 소비자들의 만족도는 고기의 조성 및 요리방법에 의하여 상당부분 좌우되는 것으로 나 타났다 (Neely et al, 1998;Savell et al, 1999 X-Z Means in the same column with different letters are significantly different (p<0.05). 1) Scale from 0 to 100, 0=extremely undesirable in flavor, extremely tough, extremely dry and extremely undesirable overall; 100=extremely desirable in fravor, extremely tender, extremely juicy and extremely desirable overall.…”
unclassified